Factors associated with performance enhancing substances use in Portuguese fitness settings - Tavares, Ana Sofia (2020)
Background: According to The Portuguese "National Plan for Reducing of Addictive Behaviors and Dependencies 2013-2020", the use of performance-enhancing substances (PES) by recreational sports practitioners is a pertinent and current topic, particularly in the field of public health. The people who use the gyms and fitness centers come from diverse socio-demographic conditions and have different purposes and motivations, which could influence the risk for PES use. In this context, and since there are practically no studies on the use of PES outside competitive sport in Portugal, it is necessary to investigate the reality of these settings, considering that the use of these substances can be associated with dangerous side effects or even fatal with long-term use. Research questions: What is the influence of socio-demographic variables, exercise profile, and smoking tobacco and alcohol habits in PES use among a sample of Portuguese gym/fitness users? Method: Cross-sectional, quantitative, and exploratory study among a convenience sample of 453 Portuguese gym/fitness users, recruited directly on social networks (Facebook) and by institutional email (via gyms). Data were collected via a structured on-line questionnaire. Statistical analysis was performed using SPSS 22. Results: Among the 453 gym/fitness users (61,3% female; 38,7% male) who participated in the survey, 50 (11,1%) reported PES use. Being male was identified as risk factors for PES use. A significant association was found between the gender and the class of PES used, namely the females presented a positive association with the use of diuretics (p = .003, C.I. 95% = .002, .004)) and males with the anabolic-androgenic steroids intake (p = .026, C.I. 95% = (.023, .029)). Being a student, versus being a worker, decreases the risk of consuming PES in 72.2%. The higher the education, the lower the risk of consuming PES in 26.9%. The frequency of training and the time spent in training are identified as risk factors for PES use. Concerning the association between modalities of physical activity and PES use, individuals who reported bodybuilding practice were more than eight times more likely to use PES, and individuals who reported Muay Thai practice, showing more than six times more likely to use PES versus individuals without bodybuilding and Muay Thai practice, respectively. There was no statistically significant association between PES use and smoking tobacco (x12 = .319, p = .992), neither in terms of consumed alcohol between users and nonusers of PES (x12 = .599, p = .439). Conclusion: This study revealed factors associated with PES use among Portuguese gym/fitness users and the increasing importance to investigate psychosocial determinants that may influence PES use in this specific population. Exploring these factors may improve the effectiveness of practical interventions to reduce the PES use among gym/fitness users.